2023
DOI: 10.3389/fonc.2023.1049855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of EGFR-TKIs combined with craniocerebral radiotherapy on the prognosis of EGFR-mutant lung adenocarcinoma patients with brain metastasis: A propensity-score matched analysis

Abstract: Background and PurposeEpidermal growth factor receptor (EGFR)-mutant lung cancers are associated with a high risk of developing brain metastases (BM). Craniocerebral radiotherapy is a cornerstone for the treatment of BM, and EGFR-TKIs act on craniocerebral metastases”. However, whether EGFR-TKIs combined with craniocerebral radiotherapy can further increase the efficacy and improve the prognosis of patients is unclear. This study aimed to evaluate the difference in efficacy between targeted-therapy alone and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Deng et al draw a similar conclusion that prolonged iPFS translates into a better OS in EGFR-mutant lung adenocarcinoma patients with BM who received TKIs combined with craniocerebral radiotherapy. 29 In contrast to our findings, another study by Deng et al showed that in low scores of Lung-molGPA patients with EGFR-mutant lung adenocarcinoma with BMs, the enhanced iPFS failed to translate to improved OS among three brain radiotherapy modes. 30 Given the correlation between iPFS and OS after intracranial local therapy for BMs of lung adenocarcinoma patients is controversial, and there are fewer relevant reports, the findings of the current study can contribute to the data in the literature database.…”
Section: Discussioncontrasting
confidence: 99%
“…Deng et al draw a similar conclusion that prolonged iPFS translates into a better OS in EGFR-mutant lung adenocarcinoma patients with BM who received TKIs combined with craniocerebral radiotherapy. 29 In contrast to our findings, another study by Deng et al showed that in low scores of Lung-molGPA patients with EGFR-mutant lung adenocarcinoma with BMs, the enhanced iPFS failed to translate to improved OS among three brain radiotherapy modes. 30 Given the correlation between iPFS and OS after intracranial local therapy for BMs of lung adenocarcinoma patients is controversial, and there are fewer relevant reports, the findings of the current study can contribute to the data in the literature database.…”
Section: Discussioncontrasting
confidence: 99%
“…It is one of the main tools for increasing local control in patients with EGFR-mutant NSCLC BMs [6, 25,26]. In a previous study we showed that EGFR-TKIs combined with craniocerebral radiotherapy improved iPFS, OS, and PFS in patients with EGFR-mutant lung adenocarcinoma with BM [27]. The current study further explored whether the combined use of bevacizumab could lead to survival bene ts in patients with EGFR-mutant NSCLC BMs undergoing cerebral radiotherapy.…”
Section: Discussionmentioning
confidence: 81%
“…It is one of the main tools for increasing local control in patients with EGFR-mutant NSCLC-BM [ 6 , 25 , 26 ]. In a previous study, we showed that EGFR-TKI combined with craniocerebral radiotherapy improved iPFS, OS and PFS in patients with EGFR-mutant lung adenocarcinoma with BM [ 27 ]. The current study further explored whether the combined use of bevacizumab could lead to survival benefits in patients with EGFR-mutant NSCLC-BM undergoing cerebral radiotherapy.…”
Section: Discussionmentioning
confidence: 99%